Application of the drought management guidelines in Morocco [Part 2. Examples of application] - Ouassou A.; Ameziane T.; Ziyad A.; Belghiti M. (Drought management guidelines technical annex, 2007)
The laws with regard to water management were seriously reviewed in 1995. The Administration is still largely in charge of the formulation of water policies. The consultative institutions issue recommendations and approve plans while the stakeholders control over municipal water through the Local Authorities, which work under the supervision of the Ministry of Interior. However, slow change is taking place. When the drought cycle is over, the activity of the national inter-government committee is abandoned. Should the drought recur, the same procedures are reproduced regardless the results of the previous drought episode. There is however a renewed political will to move away from this crisis management to a more proactive drought management approach. This has been activated in 2001 by the creation of the National Drought Observatory in the form of an institutional network of representative stakeholders working on drought issues, the support of the insurance policy plans and water saving operations. A methodology of drought characterization, risk analysis and vulnerability assessment in agricultural system is presented for Oum Er Rbia river basin.